Pitfalls in the clinical diagnosis of vertebral fractures: a case series in which posterior midline tenderness was absent. Issue 5 (20th April 2005) - D'Costa, H; George, G; Parry, M; Pullinger, R; Skinner, D; Thomas, S; Todd, B; Wilson, M
Abstract : Objective: There is widespread belief among doctors that posterior midline tenderness is virtually a prerequisite for spinal fracture in alert, sober patients without any painful distracting injury or neurological deficit. This paper examines and challenges this belief. Methods and results: We present three patients in whom significant thoracic and lumbar vertebral fractures were missed, or were thought to be "old", because of lack of posterior midline tenderness. We also present two further patients, one with a lumbar spine fracture and one with a cervical spine fracture, in whom posterior midline tenderness was absent but in whom the correct diagnosis was made. All these patients were sober and fully alert and none had a neurological deficit or a painful distracting injury. Conclusion: The absence of posterior midline tenderness does not exclude significant spinal injury. We suggest that patients should satisfy both the Canadian and British guidelines before it is decided that imaging of the cervical spine is unnecessary.